Three Dimensions of the Image of Madrid in the Works of Francisco Umbral - Li, Zhuoqun (2026)
The spatial turn of the 1960s, a crucial phenomenon in cultural studies and literary space representation, has greatly influenced literary criticism and analysis. This article focuses on the work of the prominent 20th-century Spanish writer Francisco Umbral, and his literary representation of Madrid. Through the analysis of his novels, chronicles, and his Diccionario Cheli (Dictionary of Madrid slang), we explore how Umbral merges memory, imagination, and popular speech to shape his unique vision of Madrid. This study comprises three parts: a review of spatial studies in literature, an exploration of Umbral’s trajectory and his portrayal of Madrid, and an analysis of Madrid’s three-dimensional image in his work. We conclude by highlighting how Umbral shapes his own Madrid, integrating everyday life with memory, imagination, and popular speech.